Analysis and assessment of the limiting intensities of processes forming maximum water runoff rivers of the right and left banks of the Dniester River basin - Moskalenko, Stanislav (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Introduction. The maximum flow of rivers, on the one hand, refers to extreme indicators of their water regime, which is the highest degree of danger and catastrophic situations, and on the other hand, it is a natural phenomenon that reflects the maximum potential of nature for its formation within the river basin or a certain territory. The purpose of the study is to generalize the patterns of spatial variability of the manifestations of the greatest intensity of the processes of formation of maximum runoff separately for the right-bank (Carpathians) and left-bank (Podillia) parts of the Dniester River basin, and to calculate the limiting intensities with reduction to certain catchment areas.Methods. The methods of mathematical statistics and the theory of probabilities were used in the research - correlations between random variables, Pearson's analytical distribution of type III. Initial data - series of the largest annual maximum water discharges from 44 hydrometric stations of the State Hydrometeorological Service of Ukraine on the rivers of the Dniester River basin, from the beginning of their observations to 2019 inclusive. 59% of hydrological stations have observation periods > 60 years, 32% - from 50-60 years, 9% of stations - < 50 years.Results. Analysis of the observed maximum water flows for the right-bank and left-bank parts of the Dniester River basin showed trends in their change - an increase in the maximum specific runoff (l·s⁻¹·km⁻²) of river water is observed with a decrease in the area of their catchments. However, due to different physical, geographical and hydrometeorological conditions, the maximum specific runoff of water flow from the same catchment areas for the rivers of the right-bank of the Dniester River basin are significantly higher than for the left-bank part, by about 3,5-4,5 times.Since the observation periods are different, analytical values of the maxima reduced to 1% exceedance probability were determined, approximated by a Pearson type III distribution. The constructed relationships between the maximum specific runoff of water (l·s⁻¹·km⁻²) in individual sections of rivers with 1% exceedance probability from the corresponding areas (km2) of their basins clearly showed that small and elementary catchments are marked by bright manifestations of the limiting intensity of the formation of maximum runoff on rivers. The measure of the tightness of the relationships for the right-bank and left-bank parts of the Dniester River allowed us to qualitatively characterize the obtained dependencies, respectively, as noticeable and high. This made it possible, using the obtained coupling equations, to calculate the probable maximum modules of water runoff of 1% exceedance probability from small catchment areas – 2, 5, 10, 20, 50 and 100 km2.Conclusions. The maximum specific runoff of water from elementary catchments of the right-bank (Carpathian) of the Dniester River basin with an area of 2-10 km2 can reach 7500-4500 l·s⁻¹·km⁻², and with an area of 10-20 km2 – 4500-3500 l·s⁻¹·km⁻². For the left-bank (Podillia) the intensity of the processes of formation of maximum water runoff is lower - from elementary catchments with an area of 2-10 km2 – 3200-1500 l·s⁻¹·km⁻², with an area of 10-20 km2 – 1500-1000 l·s⁻¹·km⁻². However, given the variability of hydrological processes these estimates are not absolute and should be considered indicative of potential intensities rather than precise thresholds for all locations.